READING AND REWRITING OF TWO POETS FROM MINAS GERAIS: FOR A DECOLONIAL PRACTICE IN THE CLASSROOM - Ronald Félix de Paula, Isaac; Cristina Lima Lages, Rita (Revista Gênero e Interdisciplinaridade, 2025)
This article aims to problematize some issues related to the practice of reading and writing poetry that take mining practices in the state of Minas Gerais as their theme. It is based on the experience of adolescents with poetic texts and on the practice of reading the poems of authors Adélia Prado (1986) and Carlos Drummond de Andrade (1984a, 1984b), carried out by students of the final years of elementary school in a public school. The study seeks to understand reading reception practices as well as the rewriting of poetic texts in the classroom, taking into account the students’ experiences as individuals belonging to the mining area, which is constantly subjected to environmental and social disaster risks.